A new caffeic acid ester and a new ceramide from the roots of Eriosema glomeratum. (October 2021) - Tabakam, Gaétan Tchangou; Kodama, Takeshi; Donfack, Arno Rusel Nanfack; Nguekeu, Yves Martial Mba; Nomin-Erdene, Battsengel; Htoo, Zin Paing; Do, Kiep Minh; Ngouela, Silvère Augustin; Tene, Mathieu; Morita, Hiroyuki; Awouafack, Maurice Ducret
Graphical abstract: Highlights: A new caffeic acid ester and a new ceramide were isolated from the Eriosema glomeratum root. The structures of new compounds were characterized by NMR, MS and chemical conversions. Eight known compounds were also isolated from the plants. The cytotoxicity of the isolated compounds was evaluated on three human cell lines. Two of the known compounds showed the activities against three cancer cell lines. Abstract: A new caffeic acid ester, eriocaffeate (1 ), and a new ceramide, erioceramide (2 ) along with eight known compounds, genistein (3 ), genistin (4 ), lupinisoflavone A (5 ), quercetin (6 ), lupeol (7 ), a mixture of β -sitosterol (8 ) and stigmasterol (9 ), and β -sitosterol-3-O- β -d -glucopyranoside (10 ) were obtained after the phytochemical investigation of the CH2 Cl2 /MeOH (1:1, v/v) extract from the roots of Eriosema glomeratum . The structures of the new compounds were elucidated by analyses of their spectroscopic data including 1D- and 2D-NMR, HRESI-MS, and ESI-MS/MS as well as chemical conversions. The cytotoxicity of isolated compounds 1 −6 was determined against three human [lung (A549), breast (MCF7), and cervical (HeLa)] cancer cell lines. Compounds 3 and 6 possessed the activities on all the tested three cell lines, MCF7 (IC50 = 88.9 and 42.6 μM), A549 (IC50 = 42.1 and 28.2 μM), and HeLa (IC50 = 27.4 and 19.1 μM), respectively. Compound 4 showed selective moderate activity with the IC50 value of 68.7 μM on the HeLa cancer cell line.